Politik Anggaran Pendidikan yang Minus Keberpihakan - Fathur Rahman (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2011)
This study is about the politics of pro-poor budget. Pro-poor budget is the budget set out in APDN related to the policy on the poor. The observed object is political education budget in the budget of the Semarang City, 2009. The results of this study, suggests that the education sector budget in the 2009 Budget, the Semarang City, there is no statement showing the pro-poor. Although the education sector budget increased to 35 percent of the entire budget. But in reality, its implementation is not up to the level of transparency and accountability are ineffective and inefficient. Causes of non-affirmative education sector budget policy in the 2009 Budget of Semarang is a structural factor. Hence, the needs of the poor should be the main target of budget allocations in the education sector in order to liberate the poor from poverty.